Dr. Preparation of Metoclopramide-loaded Film Dosage Forms using Natural Polysaccharides - Murata, Yoshifumi (European Journal of Applied Sciences, 2022)
Natural polysaccharides are used as pharmaceutical or food ingredients. In this study, film dosage forms (FDs) containing the model drug metoclopramide (MCP) were prepared using sodium alginate or pectin as the film base, and the preparations were modified using additives such as chitin. The dissolution profiles of MCP from the FDs in a small volume of physiological saline were investigated. All the forms immediately swelled, disintegrated in physiological saline, and were transformed into a gelatinous substance. When the FD was prepared using sodium alginate, MCP incorporated in the form gradually dissolved into the test solution. In contrast, the drug immediately dissolved if the FD was prepared with pectin. The MCP dissolution rate can be controlled by modification of the film base with suitable additives. These results suggest that FDs prepared using these water-soluble polysaccharides can be useful for administering medicines to persons that have difficulty swallowing.